Heavy metal concentrations in Ikere Gorge Dam water, Iseyin, Southwestern Nigeria - A. O. Olabamiji; C. A. Adejumobi; S. K. Alausa; R. F. Oloruntola; A. O. Ilori; J. O. Amao (Discover Water)
Abstract Water pollution poses a significant threat to human health and the overall well-being of ecosystems. Southwestern Nigeria, where the Ikere Gorge Dam is located, local water source is the major supply for daily life and agriculture purpose, there is need to ascertain the water quality. Twenty water samples were collected at each 100–200 m apart, the samples were filtered, acidified and digested, ICP-OES instrument was used to analyze the samples. The results showed the following concentration ranges: Cadmium: 0.001–0.017 mg/l, Chromium: 0.001–0.039 mg/l, Lead: 0.001–0.011 mg/l. Mercury: 0.001–0.111 mg/l, Arsenic: 0.001–0.005 mg/l, Nickel: 0.01–0.07 mg/l, Copper: 0.073–0.874 mg/l, Calcium: 29.038–293.516 mg/l, Iron: 4.840–49.119 mg/l and Potassium: 9.631–97.839 mg/l. Eighty percent of the samples were higher the global acceptable limit, three percent were within safe limit values, seven percent were below the recommended value. Exposure level of Cr, Cu, As were higher than the safe limit. Similarly, Cd, As and Hg have HQ > 1 indicating high risk non-carcinogenic health effects. In contrast, Cr, Pb, Cu, Ni, Zn, Fe, Mn have HQ < 1. ELCR values of Cd and As were higher than the acceptable limit, Cu, Hg, Ni, Zn, Fe, Mn, had no ELCR values. These findings recommended the need for improved water management in Nigeria, the need for long-term strategies to address population growth, climate change, and clean water for every nation, in line with United Nations Sustainable Development Goals 6 &7.